Extended role of transnasal oesophagoscopy: a review of the literature. Issue 6 (18th June 2020) - Johnstone, L; Tassone, P; Burrows, S; Nassif, R; Vijendren, A
Abstract: Background: Advances in endoscopic technology have allowed transnasal oesophagoscopy to be used for a variety of diagnostic and therapeutic procedures. Method: A review of the literature was carried out to look into the extended role of transnasal oesophagoscopy within otolaryngology, using the Embase, Cinahl and Medline databases. Results: There were 16 studies showing that transnasal oesophagoscopy is safe and cost effective and can be used for removal of foreign bodies, tracheoesophageal puncture, laser laryngeal surgery and balloon dilatation. Conclusion: This study presents a summary of the literature showing that transnasal oesophagoscopy can be used as a safe and cost-effective alternative or adjunct to traditional rigid endoscopes for therapeutic procedures.